FACTORS THAT INFLUENCE PSYCHIATRIC CLINICAL LEARNING EXPERIENCE FOR DIPLOMA NURSING STUDENTS IN WESTERN KENYA - Wesonga, Janet; Kipmerewo , Mary; Ochanda, Damaris (Journal of Health, Medicine and Nursing, 2021)
Purpose: This study investigated factors that influence psychiatric clinical learning for diploma nursing students in western Kenya. Methodology: Cross-sectional research design was used with both qualitative and quantitative approaches in data collection. Study participants consisted of diploma nursing students on psychiatric clinical placement. Ten institutions that place their students at Kakamega County Referral Hospital for psychiatric experience were sampled. A total of 178 students, 10 lecturers and 3 psychiatric nurses participated in the study. Qualitative data was collected using interview guides; while quantitative data was collected using structured questionnaires. Descriptive statistics were used to analyse quantitative data while qualitative data was analysed thematically. The relationship between variables was set at a statistical significance of p-value < 0.05. Quantitative data was coded and entered the Statistical Package for Social Sciences version 25.0. Continuous variables were summarized using the Odds Ratio to measure the association between variables and presented in tables and figures to provide a pictorial description of the sample. Findings: The results showed that most students were theoretically prepared to participate in psychiatric clinical learning (67.8% - OR: 1.4: 95% p=0.3). Also, it was supported by the students having a positive attitude (66.1% - OR: 1.2; p=0.5) and being motivated (64.5% - OR: 1.5; p=0.2) towards clinical placement. However, according to key informants' findings, most students were not well prepared in practical skills for clinical placement at the psychiatric unit, which was due to inadequate or lack of simulative laboratory for practice at the college level. Nursing students were well prepared theoretically to engage in psychiatric clinical learning placement at Kakamega County Referral Hospital. It also, established that positive attitude and motivation from the nursing students towards clinical placement at the psychiatric unit promoted clinical learning experience and performance thereafter. However, most of the psychiatric nursing students were not well prepared with practical skills to handle mentally-ill patients Conclusion: This study revealed that Kenya Registered Community Health Nurse diploma students were well prepared theoretically to engage in psychiatric clinical learning placement. Recommendation: Medical colleges in Kenya should emphasise skill-based training on human anatomy and behaviour through simulation. Trainers should be required to lead the nursing students through skill-based training. Medical college management should make available practical based resources to trainers and students to promote a skill-based learning approach. Unique contribution to theory, practice and policy Practical skills should be given priority at the college level when preparing students for clinical placement for a holistic clinical learning experience. Positive attitude and motivation from the nursing students towards clinical placement at the psychiatric unit promoted clinical learning experience and performance thereafter.